2021
DOI: 10.1186/s12913-021-06996-y
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of removing performance-based financial incentives on community health worker motivation? A qualitative study from an infant and young child feeding program in Bangladesh

Abstract: Background Community health worker (CHW) motivation is an important factor related to health service quality and CHW program sustainability in low- and middle-income countries. Financial and non-financial motivators may influence CHW behavior through two dimensions of motivation: desire to perform and effort expended. The aim of this study was to explore how the removal of performance-based financial incentives impacted CHW motivation after formal funding ceased for Alive and Thrive (A&T), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Two key intermediate outcomes-job satisfaction and job readiness-increased over the program period but this improvement was not sustained. Our previous research has indicated that this may be directly attributable to the end of A&T: removal of incentives has been shown to negatively impact BRAC health workers' IYCF service delivery quality (42) and desire to perform (43). Alive & Thrive was designed as a "proof of concept" initiative: if it demonstrated success, then governments would have the evidence necessary to implement it.…”
Section: Discussionmentioning
confidence: 99%
“…Two key intermediate outcomes-job satisfaction and job readiness-increased over the program period but this improvement was not sustained. Our previous research has indicated that this may be directly attributable to the end of A&T: removal of incentives has been shown to negatively impact BRAC health workers' IYCF service delivery quality (42) and desire to perform (43). Alive & Thrive was designed as a "proof of concept" initiative: if it demonstrated success, then governments would have the evidence necessary to implement it.…”
Section: Discussionmentioning
confidence: 99%
“…Our stakeholders also talked about providing additional performance-based monetary incentives to CHWs to motivate them to visit more households and recruit new members. Previous research in Bangladesh has shown that monetary incentives positively impact CHW’s retention and intervention success [ 44 , 45 ]. Our interviewees also suggested incorporating non-health benefits in the benefits package to encourage their membership renewal.…”
Section: Discussionmentioning
confidence: 99%
“…Health center and NGO providers alike emphasized the importance of on-going training and motivation to address high attrition, which has been noted elsewhere when relying on unpaid CHWs [47]. Sufficient compensation, healthcare system support, and well-defined job responsibilities are critical factors for sustainable implementation of CHW programs [48,49]. Further investigation into the educational components of STMMs is needed, both to ascertain the effectiveness of knowledge transfer among providers and the impact on community health literacy.…”
Section: Investing In Health Educationmentioning
confidence: 99%